Homage to Mar Cariattil : pioneer Malabar ecumenist. - Payngot, Charles (Kottayam, Kerala, India : Oriental Institute of Religious Studies India Publications, 1992)
On the life and work of Mar Cariattil, 1742-1786; contributed articles.
Bibliogr. Index. Append.
0027
Keywords: Kariyatti, Yauseppa, -- 1742-1786.; Syro-Malankara Church; Christians -- India -- Kerala -- Biography; Kerala (India) -- Biography